How effective are trading pauses? - Hautsch, Nikolaus; Horvath, Akos (Journal of Financial Economics, 2019)
Exploiting Nasdaq order book data and difference-in-differences methodology, we identify the distinct effects of trading pause mechanisms introduced on US stock exchanges after May 2010. We show that the mere existence of such a regulation makes market participants behave differently in anticipation of a pause. Pauses enhance price discovery during the break but have adverse effects on price stability and liquidity after the pause. We find that pauses ultimately do not “cool off” markets but cause extra volatility. This implies a regulatory trade-off between the protective role of trading pauses and their adverse effects on market quality.